2005
DOI: 10.1189/jlb.1104694
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT enhances the bactericidal activity of human monocytes and neutrophils via HVEM

Abstract: Human monocytes and neutrophils play major roles in clearing bacteria from human blood and tissues. We found that the herpes virus entry mediator (HVEM) was highly expressed in monocytes and neutrophils, and its interaction with "homologous to lymphotoxins, shows inducible expression, and competes with herpes simplex virus glycoprotein D for HVEM/tumor necrosis factor (TNF)-related 2" (LIGHT) enhanced bactericidal activity against Listeria monocytogenes and Staphylococcus aureus. The LIGHT-HVEM interaction inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 37 publications
4
79
1
6
Order By: Relevance
“…Mammalian LIGHT has been shown to be expressed on T cells and immature dendritic cells (24,25) and is instrumental in T cell homeostasis and stimulation of monocyte and neutrophil bactericidal activity via the herpes virus entry mediator receptor (26). The highest constitutive expression of LIGHT in unstimulated rainbow trout was observed in the spleen, PBL, gill, kidney, and intestine (Fig.…”
Section: Light (Tnfsf 14) and 4-1bbl (Tnfsf 9)mentioning
confidence: 95%
“…Mammalian LIGHT has been shown to be expressed on T cells and immature dendritic cells (24,25) and is instrumental in T cell homeostasis and stimulation of monocyte and neutrophil bactericidal activity via the herpes virus entry mediator receptor (26). The highest constitutive expression of LIGHT in unstimulated rainbow trout was observed in the spleen, PBL, gill, kidney, and intestine (Fig.…”
Section: Light (Tnfsf 14) and 4-1bbl (Tnfsf 9)mentioning
confidence: 95%
“…Our findings in experimental HF suggest that this receptor can also be expressed in cardiomyocytes, with particularly high expression in the failing myocardium. LIGHT has been reported to promote several effects relevant to HF, such as production of inflammatory cytokines, matrix degradation, and increased production of reactive oxygen species in leukocytes, endothelial cells, and fibroblasts [13,16,22]; some of these effects seem to involve LIGHT-HVEM interaction. Furthermore, studies in animal models suggest that LIGHT-HVEM interaction may play a major role in inflammatory bowel disease, allograft rejection, and graft-versus-host disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…In activated monocytes, macrophages and neutrophils, LIGHT led to an increased expression of cytokines, such as IL-8 and TNF-a and matrix metalloproteinases, such as matrix metalloproteinase-9. 22,29,31 In Human umbilical vein endothelial cells, LIGHT induced the secretion of chemokines (IL-8 and GRO) and cell-surface expression of adhesion molecules (intercellular adhesion molecule-1 and vascular cell adhesion molecule-1).…”
Section: Discussionmentioning
confidence: 99%
“…Among the multiple biological activities described, LIGHT is known to stimulate the expression and/or secretion of various molecules involved in the inflammatory response. 14,22,29,31 Given this background, we studied the secretion of 21 cytokines by human differentiated adipocytes under different LIGHT concentrations. The results showed that differentiated adipocytes from obese subjects spontaneously released pro-inflammatory cytokines Table 4 Diagram showing the changes of cytokine secretion by human differentiated adipocytes incubated with 0, 10, 100 and 1000 ng ml À1 human LIGHT for 24 h…”
Section: Discussionmentioning
confidence: 99%